2020
DOI: 10.3989/gya.0806192
|View full text |Cite
|
Sign up to set email alerts
|

Structure and thermal properties of beeswax-based oleogels with different types of vegetable oil

Abstract: Beeswax-based oleogels with different types of vegetable oil, including camellia oil (CO), soybean oil (SO), sunflower oil (SFO), or flaxseed oil (FO), were prepared and their structure and thermal properties were evaluated. The critical concentration of oleogel obtained from each of CO, SO, and SFO at 25 °C was 3% (w/w), and that from FO was 4%. Thermal measurements revealed similar thermodynamic curves for oleogels in different lipid phases. X-Ray diffraction showed orthorhombic perpendicular subcell packing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
(37 reference statements)
6
24
0
Order By: Relevance
“…In this regard, we can conclude that the oil type in the beeswax oleogel is not related to changes in the vibrational characteristics of the hydrocarbon chain of the beeswax molecules during crystallization. The absence of changes in melting and crystallization peaks between samples is consistent with the work [ 40 ], which obtained similar thermograms of oleogels based on vegetable oils and showed that the thermal curve largely depends on the concentration and type of gelating agent, regardless of the oil phase. TPM, crystal size, and T m can be distinguished into separate clusters with a close positive correlation with each other.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In this regard, we can conclude that the oil type in the beeswax oleogel is not related to changes in the vibrational characteristics of the hydrocarbon chain of the beeswax molecules during crystallization. The absence of changes in melting and crystallization peaks between samples is consistent with the work [ 40 ], which obtained similar thermograms of oleogels based on vegetable oils and showed that the thermal curve largely depends on the concentration and type of gelating agent, regardless of the oil phase. TPM, crystal size, and T m can be distinguished into separate clusters with a close positive correlation with each other.…”
Section: Resultssupporting
confidence: 91%
“…The absence of changes In melting and crystallization peaks between samples is consistent with the work [ 40 ], in which similar thermograms of oleogels, based on vegetable oils, were obtained, and it was shown that the thermal curve depends largely on the concentration and type of structure-forming agent, regardless of the oil phase. At the same time, our study found an additional melting peak around 37 °C in the thermogram of LO oleogels, which may be an indication of the formation of two types of crystals ( Figure 1 B).…”
Section: Resultssupporting
confidence: 91%
“…The mechanical properties of gelled materials were assessed at low deformation (up to 50%) according to a prior study by Pang et al [ 8 ] in order to correctly mediate the effect of both external and internal surface structure on texture. In particular, values of textural attributes as a function of either fiber addition or cooling temperature were reported for EVO- ( Figure 3 ) and SFO- ( Figure 4 ) based systems, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The great potential of oleogelated systems is related to a full substitution of solid fats with gels containing unsaturated or poly-unsaturated edible oil in their native form [ 5 ]. Besides, the gelling agents not only enable preserving the nutritional characteristics of the oil but could even preserve them from oxidation phenomena to which unsaturated bonds are prone to be subjected [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the d spacing values from the XRD study, one can suggest a probable molecular packing arrangement in the self-assembled gel state [32]. Wax-based oleogels display similar XRD patterns of orthorhombic perpendicular subcells and β polymorphic forms; for this reason they are highly suitable for the replacement of those fats which offer plasticity and mouthfeel to the food product [33,34]. An exception is reported for beeswax oleogel, which exhibited in the small diffraction angles only one peak at a low d-value (0.415 nm), which is a characteristic of a hexagonal symmetry [35].…”
Section: Oleogel's Building Unitsmentioning
confidence: 99%